Evidence for a 'window of opportunity' in hidradenitis suppurativa treated with adalimumab: a retrospective, real‐life multicentre cohort study. (1st January 2021) - Marzano, A.V.; Genovese, G.; Casazza, G.; Moltrasio, C.; Dapavo, P.; Micali, G.; Sirna, R.; Gisondi, P.; Patrizi, A.; Dini, V.; Bianchini, D.; Bianchi, L.; et al.
Summary: Background: The anti‐tumour necrosis factor (TNF)‐α adalimumab is the only licenced biologic for moderate‐to‐severe hidradenitis suppurativa (HS). No predictors of response have been identified so far. Objectives: To identify clinical parameters predicting response to adalimumab and confirm its efficacy/safety. Methods: The data of 389 patients with HS treated with adalimumab in 21 Italian centres were reviewed. Sex, age at onset/diagnosis/baseline, body mass index, smoking, phenotype, previous treatments, concomitant antibiotics and 'therapeutic delay', defined as the time from HS onset to adalimumab initiation, were assessed. Response to adalimumab and its impact on quality of life (QoL) were evaluated using the Hidradenitis Suppurativa Clinical Response (HiSCR) and the Dermatology Life Quality Index (DLQI) or the Visual Analogue Scale for pain (VAS pain), respectively. Logistic regression analysis was performed. Results: The therapeutic delay correlated to lack of response to adalimumab at week 16 [odds ratio (OR) 1·92 for therapeutic delay > 10 years; 95% confidence interval (CI) 1·28–2·89; P = 0·0016). HiSCR was achieved in 43·7% and 53·9% patients at week 16 and 52, respectively. Significant reductions in both DLQI and VAS pain were found between week 16 vs. baseline ( P < 0·0001 for both) and week 52 vs. baseline ( P < 0·0001 for both). Previous immunosuppressants inversely correlated to HiSCR at week 52 (OR = 1·74, 95% CI 1·04–2·91, P = 0·0342). Conclusions: Inverse correlation between therapeutic delay and clinical response was found, supporting early adalimumab use and providing evidence for a 'window of opportunity' in HS treatment. Adalimumab efficacy and safety were confirmed, along with patients' QoL improvement. Immunosuppressants could negatively influence the response to adalimumab inducing a switch to non‐TNF‐α‐driven pathways.